Research of biophysical properties of biologically active points under influence the stress of factors (Experimental biology, 2015)
Biophysical properties of aurikulyarny bioactive points of skin of animals under influence a stress of factors ofenvironment are investigated. The raised indicators of conductivity in all biologically active points of skin of animalsunder the influence of noise in comparison with norm are found. Change of indicators of biopotentials of bioactivepoints of skin of animals being under vibration concerning norm is proved. There is no special difference in biophysicalindicators of biologically active points left and right ear sinks.
Keywords: conductivity; biopotential; frequency; aurikulyarny; biologically active points; dynamics; days; decibel; noise; vibration